Effective role of aromatherapy in reducing big little problem-postoperative nausea and vomiting: A systematic review - Sona Pashaei; Nuray Akyüz (Wolters Kluwer Medknow Publications, 2024)
Postoperative nausea and vomiting (PONV) are common and distressing side effects after surgery and anesthesia. Pharmacological treatment is not sufficient to manage these two symptoms. Although the use of certain anesthetic agents is considered the main basis for this phenomenon, the exact factors are unknown. Aromatherapy is effective in reducing PONV in adults. The aim of this review is to scan the studies evaluating the effect of aromatherapy on the management of nausea and vomiting in the postoperative. A literature search was performed by scanning Cochrane Reviews, PubMed, OVID, Sciences Direct, and Google Scholar. Keywords "aromatherapy," "use of aromatherapy," "aromatherapy oils," "nausea," "vomiting," "postoperative nausea and vomiting," and "PONV" combined with Boolean operators, including AND, OR, and NOT. Data gathered from studies published from 2013 to 2023 were reviewed for the effect of aromatherapy on PONV. As a result of the screening, 12 studies out of a total of 706 studies were examined based on the inclusion criteria. In the studies, aromatherapy was used either by inhalation or orally. The plants that were used the most in these studies were ginger and mint. When the literature was reviewed, it was found that aromatherapy reduced the rate of nausea and vomiting and the need for antiemetics, especially in the first minutes after surgery. Using aromatherapy in surgical patients may relieve common postoperative symptoms. The limitations of drug therapy have led to an increase in the use of alternative drugs for the management of nausea and vomiting. Aromatherapy was favored by most patients and is an effective treatment option for PONV.